The anticommunism of the chilean juventude conservadora: the case of the Falange Nacional (1935-1957) - Gabriela Gomes (Mediações: Revista de Ciências Sociais, 2014)
The trajectory of the Juventude Conservadora (Conservative Youth) in the Falange Nacional (National Phalanx) showed a radical break with the political project of one of the parties of the traditional right, the Partido Conservador (Conservative Party, 1851). Inspired by the doctrine of Christian humanism, the Phalangist project became the Partido Democrata Cristão (Christian Democratic Party, 1957). In this article, the Phalangists’ perceptions of communism and the importance given to the Partido Comunista (Communist Party) as a legitimate actor in the party system are analyzed.